2011
DOI: 10.1007/s11999-011-1867-1
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Complications of Open Intramedullary Nailing of Midshaft Clavicle Fractures With the Rockwood Clavicle Pin

Abstract: Background Intramedullary clavicle fixation is a potential alternative to plate fixation. Previous studies documenting the complication rates of intramedullary clavicle fixation have demonstrated variable rates of soft tissue complications and fracture healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…The RCP intended to provide a less invasive alternative to plate fixation. However, the incidence of complications of RCP was relatively higher, including nonunion, revision surgery, and soft tissue complications [28]. The high complications may be related to the inherent weak biomechanical stability of the RCP.…”
Section: Discussionmentioning
confidence: 99%
“…The RCP intended to provide a less invasive alternative to plate fixation. However, the incidence of complications of RCP was relatively higher, including nonunion, revision surgery, and soft tissue complications [28]. The high complications may be related to the inherent weak biomechanical stability of the RCP.…”
Section: Discussionmentioning
confidence: 99%
“…The subcutaneous position of the IM device contributes to the overlying skin necrosis posteriorly, which is clearly a concern for bacterial seeding of the implant, although deep infections or microbiologically confirmed infections are rarely reported in literature. 13,15 We also found only two patients with positive microbiology results, which may suggest a primary inflammatory process rather than an infective one. The senior surgeons became suspicious about the apparent increase in wound complications and during the last IM fixation undertaken on a young male, noted blackening and heating of the guide wire used for retrograde drilling.…”
mentioning
confidence: 67%
“…5 Wijdicks et al suggested that infection is defined as redness, swelling, purulent discharge, a positive wound culture, and/or when prescription of antibiotics was given, and irritation was caused by prominence or protrusion of the implant material. 6 There are only few articles [7][8][9][10][11][12][13] reporting on these complications and even fewer 14,15 explore their treatments and outcomes, especially with IM cannulated screws. 16,17 Our study was designed to focus on the treatment and outcome of patients with clavicle fractures treated with open reduction and internal fixation, who had local wound complications.…”
Section: Introductionmentioning
confidence: 99%
“…14,[23][24][25][26][27][28][29][30][31][32] In addition, 6 studies included treatment of nonunions or delayed unions and did not make a distinction with the treatment of acute fractures when describing the complications, 16,33-37 2 studies were surgical technique papers, 38,39 1 study reported on plate fixation, 40 1 study lacked a definition for dislocation, 41 1 study did not make a distinction between angulation and comminution, 42 1 study included fewer than 10 patients 15 and, in 1 study, 11 authors reported on a previously reported patient population. Reported rates for major complications like bonehealing problems and deep infections requiring implant removal were no higher than 7%.…”
Section: Discussionmentioning
confidence: 99%